Lejeunea streimannii (Lejeuneaceae, Marchantiophyta), a remarkable new species with robust stems and 5(or 6)-keeled perianths from Papua New Guinea - Wei, Yu-Mei; Tang, Qi-Ming; Zhu, Rui-Liang (Phytotaxa, 2018)
Lejeunea streimannii, a new species from Papua New Guinea, is described and illustrated. The new species is characterized by the dioicous plants, robust stem with 18‒21 rows of cortical cells and a ventral merophyte 4‒6 cells wide, ovate leaves with a rounded, strongly incurved leaf apex, small lobules with unicelluar first tooth and blunt second tooth, large underleaves with a cordate base, inflated perianths with 5(or 6) crenate, slightly winged keels.